Digital Mirror Device Application in Reduction of Wave-front Phase Errors - Zhang, Yaping (Molecular Diversity Preservation International (MDPI), 2009)
In order to correct the image distortion created by the mixing/shear layer, creative and effectual correction methods are necessary. First, a method combining adaptive optics (AO) correction with a digital micro-mirror device (DMD) is presented. Second, performance of an AO system using the Phase Diverse Speckle (PDS) principle is characterized in detail. Through combining the DMD method with PDS, a significant reduction in wavefront phase error is achieved in simulations and experiments. This kind of complex correction principle can be used to recovery the degraded images caused by unforeseen error sources.